1990
DOI: 10.1017/s0022112090002117
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of an incompressible turbulent boundary layer in the vicinity of separation

Abstract: The following is an investigation into the effects of small changes in the static pressure distribution on the development of an axisymmetric, incompressible, turbulent boundary layer with incipient separation. The pressure distribution was closely controlled to study three cases, in which the skin friction was either approximately zero, slightly negative, or slightly positive along a fixed length. Mean flow and turbulence structure in air were measured using pulsed-wire and hot-wire anemometry.These measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 15 publications
4
46
0
1
Order By: Relevance
“…The experiments on separation of a flat plate turbulent boundary layer include the works of Perry & Fairlie (1975), Simpson et al (1977Simpson et al ( , 1981a, Dengel & Fernholz (1990), Driver (1991) and Alving & Fernholz (1996, 1995. Some of these investigations have also tried to develop different scalings of the velocity profile in both outer and inner variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments on separation of a flat plate turbulent boundary layer include the works of Perry & Fairlie (1975), Simpson et al (1977Simpson et al ( , 1981a, Dengel & Fernholz (1990), Driver (1991) and Alving & Fernholz (1996, 1995. Some of these investigations have also tried to develop different scalings of the velocity profile in both outer and inner variables.…”
Section: Methodsmentioning
confidence: 99%
“…They compared the Durbin-Belcher and Perry-Schofield scalings, with the conclusion that the latter works better than the former. However, they did not actually use the velocity scale proposed by Perry & Schofield (1973), but rather determined their velocity scale so that the velocity profiles close to separation collapse with the profile given by Dengel & Fernholz (1990).…”
Section: Methodsmentioning
confidence: 99%
“…9 shows the reverse-flow factors, which means the percentage of negative streamwise velocities from the total measurement data. If the value of the reverse-flow factor is 50%, that location approximately indicates the dividing streamline or reattachment length at Y/H=0 position (Dengel and Fernholz [20]). Siller and Fernholz [9] reported that the reverseflow region was only reduced in the time mean data.…”
Section: Resultsmentioning
confidence: 99%
“…The separation bubble in experiments is defined as the region where at least 50% back flow at the wall is developed, i.e., the wall back flow coefficient wall 0:5. According to Dengel and Fernholz [18], was extrapolated to the wall from the data points in the region y 1:5 to 10 mm in order to estimate wall . The resulting geometrical properties such as the separation location x sep , the reattachment location x att , the length l sep as well as the height of the separation bubble h sep [defined as Uh sep 0] are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%